2020
DOI: 10.3390/ijms21030764
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals against TNFα-Mediated Neuroinflammatory Diseases

Abstract: Tumor necrosis factor-alpha (TNF-α) is a well-known pro-inflammatory cytokine responsible for the modulation of the immune system. TNF-α plays a critical role in almost every type of inflammatory disorder, including central nervous system (CNS) diseases. Although TNF-α is a well-studied component of inflammatory responses, its functioning in diverse cell types is still unclear. TNF-α functions through its two main receptors: tumor necrosis factor receptor 1 and 2 (TNFR1, TNFR2), also known as p55 and p75, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 145 publications
(106 reference statements)
1
33
0
Order By: Relevance
“…Unfortunately, the use of thalidomide in animal disease models and humans has proved difficult to translates as an approach to reduce neuroinflammation accompanying neurodegeneration [ 42 ] consequent to the development of intolerable off-target actions that proved dose-limiting prior to clinically relevant TNF-α lowering anti-inflammatory effects, as evidenced in a recent human Alzheimer’s disease thalidomide clinical trial [ 43 ]. This prompted a recently initiated lenalidomide Alzheimer’s disease clinical trial (MCLENA-1) [ 44 ], as lenalidomide is a more potent second-generation analog against TNF-α within the IMiD drug class [ 45 ]. Additionally, there is well-documented teratogenic sequela with this drug class that, although not potentially relevant for Alzheimer’s patients due to their age, may be relevant for TBI subjects, thereby motivating the search for new compounds that are less encumbered by prohibitive adverse actions [ 32 , 41 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the use of thalidomide in animal disease models and humans has proved difficult to translates as an approach to reduce neuroinflammation accompanying neurodegeneration [ 42 ] consequent to the development of intolerable off-target actions that proved dose-limiting prior to clinically relevant TNF-α lowering anti-inflammatory effects, as evidenced in a recent human Alzheimer’s disease thalidomide clinical trial [ 43 ]. This prompted a recently initiated lenalidomide Alzheimer’s disease clinical trial (MCLENA-1) [ 44 ], as lenalidomide is a more potent second-generation analog against TNF-α within the IMiD drug class [ 45 ]. Additionally, there is well-documented teratogenic sequela with this drug class that, although not potentially relevant for Alzheimer’s patients due to their age, may be relevant for TBI subjects, thereby motivating the search for new compounds that are less encumbered by prohibitive adverse actions [ 32 , 41 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor-alpha (TNF-α), a classical inflammation cytokine, exerts multiple functions in the nervous system by binding to two types of TNF-α receptor (TNFR1 and TNFR2) [ 16 , 17 ]. Soluble TNF-α (17 kDa) preferentially binds to TNFR1, leading to neuroinflammation and cell death [ 18 20 ], while transmembrane TNF-α (22 kDa) primarily binds to TNFR2 that mediates neuroprotective effects [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that NO and iNOS overproduction increases oxidative stress and is related to various neurodegenerative diseases [ 6 , 21 , 22 ]. Additionally, the release of proinflammatory cytokines (TNF-α, IL-1β, and IL-6) by microglia is increased during neuroinflammation [ 23 , 24 ]. In our study, chloroform- and hexane-soluble fractions of A. holophylla and their active compounds significantly inhibited the LPS-induced ROS and NO production with increased COX-2 and PGE2 expression.…”
Section: Discussionmentioning
confidence: 99%